Product carbon footprint analysis for the packaging process of returnable glass and pet containers for a South African carbonated soft drinks business - Ivanov, Ivan (My University, 2016)
Non-renewable resources are becoming scarce and current Global Warming Potential (GWP) values are rising. In an effort to promote a successful shift towards a “greener’ planet, governments worldwide are developing policies, which enforce businesses to contribute to the effort. One such policy is the potential upcoming carbon tax (measured in weight of C02e) in South Africa. As a result, industries need to carefully analyse and understand their core processes and their impact on the environment to ensure that their operations have the lowest environmental cost possible. One such industry in South Africa is the fast growing Carbonated Soft Drinks (CSD) beverage packaging industry. CSD are packaged in both Returnable Glass Bottles/Glass (RGB) and PET containers. The Product Carbon Footprint (PCF) of the CSD packaging process for 300ml Glass and 500ml PET containers was of particular interest. Review of academic literature revealed that no similar research has been conducted previously in South Africa. International studies on PCF, which vastly use the (ISO 14040/14044, 2006) for their method, were found to have conflicting results and conclusions regarding the “greenness” of the two types of containers both with respect to the overall GWP of each and the percentage contribution of the packaging process life cycle stage to the total environmental impact. This is mainly because such studies are region and technology specific. A study was therefore required to understand the implications the business' Glass and PET CSD packaging process has on its GWP and hence carbon tax. The GHG (Green House Gas) Protocol PCF guideline (World Resource Institute, 2013) was used to construct the method for this research to ensure best practice, which would allow the study to be expanded into a full blown Fife Cycle Assessment (FCA) as future work. It was found that the 500ml PET packaging process draws 100% of its Cumulative Energy Demand (CED) from purchased electricity (generated by burning coal) and has a GWP of 65 147 gCCTe/hl (hectolitre), which is 4.5 times less than that for 300ml Glass (294 173 gCCEe/hl) which has 71% of its emissions resulting directly from coal fired boilers on site. A dynamic model analysis revealed that packaging in larger containers results in a significant GWP reduction per volume for both Glass and PET containers. It was recommended that short term the business needs to focus on optimising its packaging lines’ equipment, work with suppliers on reducing the weight of the raw materials used for the packaging containers manufacture and promote rate of return of its Glass.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand. partly in fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg 2016
Keywords: Recycling (Waste, etc.); Plastic scrap; Renewable natural resources